The Use of Supplementary Materials in EFL Classes: A comparative analysis of public and private high schools - Apunte Zambrano, Deysi Paola (2012)
The topic I investigate is about “The use of supplementary materials in EFL classes: a comparative analysis of public and private high schools”. The purpose of this investigation is to analyze the variety of materials used in public and private high schools through observing classes. Students and teachers were interviewed in order to know how students acquire the knowledge. The investigation took place in a public and a private high school. Students from 1st, 2nd, and 3rd years of senior high school were the population to this investigation. The methods used in this investigation were qualitative and quantitative and the collected data was explored, analyzed, described, and compared. The qualitative method consisted on the description of the different kinds of materials used by teachers in each class. This data was collected in data collection formats. The qualitative method consisted on the use of surveys to interview teachers and students, besides note – takings were done by the interviewer to obtain more information. In conclusion, supplementary materials helped students to learn better because teachers could take into account the differences in learning.